City on Fire : Technology, Social Change, and the Hazards of Progress in Mexico City, 1860-1910 - Alexander, Anna Rose (Book collections on Project MUSE., 2016)
"City on Fire is a chronicle of progress and danger, that integrates urban environmental history with histories of technology, science, and medicine to reveal how Mexico City changed in response to the growing threat of fire in the urban center"--